dfunc5_3 - dx(3,1) = (-(k1+k2)*x(1,1) + k2*x(2,1))/m1;...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
function dx = dfunc5_3(t, x) f global m1 m2 k1 k2 k3; g dx = zeros(4,1); d dx(1,1) = x(3,1); dx(2,1) = x(4,1);
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: dx(3,1) = (-(k1+k2)*x(1,1) + k2*x(2,1))/m1; dx(4,1) = (k2*x(1,1) - (k2+k3)*x(2,1))/m2;...
View Full Document

Ask a homework question - tutors are online